Judicial Reasoning on Child Custody for Fathers Convicted of Domestic Violence: A Maqasid Al-Syari‘ah Analysis of Decision Number 1257/Pdt.G/2024/PA.Mlg - Risma Nur Arifah; Roswita Adelia Syaharani; Hersila Astari Pitaloka; Khoirul Umam (JURNAL AT-TURAS, 2026)
The determination of child custody in divorce proceedings is a central issue in Islamic family law, particularly where psychological domestic violence has been judicially established and may produce long-term harm to the child. This article examines Decision No 125/Pdt.G/2024/PA.Mlg of the Malang Religious Court, which awarded custody of a noun-mumayyiz child to the father notwithstanding proven psychological abuse. The stusy addresses the normative question: to what extent is the court’s custody reasoning consistent with al-Shatibi’s maqashid al shari’ah, particularly the protection of life/ psychological integrity (hifz al nafs) and lineage (hifz al-nasl), alongside hifz al din, when applied to cases involving psychological violence? Using a normative juridical method with a case approach, the research analyzes the judgment as primary legal material and examines the Compilation of Islamic Law, fiqh and maqashid literature, and developmental psychological assessment or structured evaluation of future risk. Applying al Shatibi’s maqashidas a hierarchy of protections, this article argues that such reasoning risks reducing maslahah to immediatefactual benefits and under-protecting the child’s long-term framework for integrating long-term child protection standarts (risk and impact assessment) into Islamic judicial reasoning on custody in domestic violence contexs.